2019
DOI: 10.1556/2006.8.2019.07
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and problematic Facebook use in adolescents: The mediating role of metacognitions

Abstract: Background and aims: Recent research used attachment theory and the metacognitive tenet as frameworks to explain problematic Facebook use (PFU). This study aims to test, in a single model, the role of different attachment styles and metacognitions in PFU among adolescents. Methods: Two separate studies were conducted in order to establish the link between security (Study 1) and insecurity (Study 2), metacognitions, and PFU. A total of 369 and 442 Italian adolescents (age: 14-20 years old) participated in Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 79 publications
3
20
0
1
Order By: Relevance
“…As a new type of behavioral addiction, SNS addiction has received much scholarly attention globally in recent years, and there are numerous studies exploring the risk factors linked to SNS addiction (Marino et al, 2018a,b). Prior studies found that attachment, especially insecure attachment, is closely related to SNS general use and addiction (Blackwell et al, 2017;Monacis et al, 2017;Flynn et al, 2018;Worsley et al, 2018a,b;Chen, 2019;D' Arienzo et al, 2019;Marino et al, 2019). Our results are consistent with prior findings.…”
Section: The Association Between Insecure Attachment Orientation Andsupporting
confidence: 92%
See 1 more Smart Citation
“…As a new type of behavioral addiction, SNS addiction has received much scholarly attention globally in recent years, and there are numerous studies exploring the risk factors linked to SNS addiction (Marino et al, 2018a,b). Prior studies found that attachment, especially insecure attachment, is closely related to SNS general use and addiction (Blackwell et al, 2017;Monacis et al, 2017;Flynn et al, 2018;Worsley et al, 2018a,b;Chen, 2019;D' Arienzo et al, 2019;Marino et al, 2019). Our results are consistent with prior findings.…”
Section: The Association Between Insecure Attachment Orientation Andsupporting
confidence: 92%
“…Although SNSs have considerable benefits, excessive use of SNS has been found to have detrimental effects on human behavior (Marino et al, 2018a). Therefore, many scholars have explored factors associated with SNS addiction, among which attachment has received much attention (Blackwell et al, 2017;Monacis et al, 2017;Flynn et al, 2018;Worsley et al, 2018a;Chen, 2019;D' Arienzo et al, 2019;Marino et al, 2019). However, the underlying mechanisms between attachment and SNS addiction remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they prefer indirect relationships, using social media, to face-to-face relationships (e.g. Facebook); this will increase the time spent on social media, resulting in an increased risk of internet addiction [23,24]. On another hand, people with a secure attachment style have high self-esteem and do not have any difficulty sharing their feelings with others, making them able to manage time spent on social media without becoming addict [7].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the anxious type was associated with higher social networking addiction because people of this type make huge efforts to be accepted by others. They also fear face-to-face interactions and have, through social networking, the advantage of choosing the time for interacting with other people and the way they present themselves to others [23,24]. The avoidant type is also correlated with higher social networking addiction since these people satisfy their social needs through online platforms while keeping a safe distance [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [7,[12][13][14] has shown that PFU is associated with negative mental health consequences (e.g., depression, anxiety, insomnia, and stress), and difficulties in interpersonal relationships. Additionally, previous findings have indicated that negative parent and peer attachment were associated with PFU [15][16][17]. Negative attachment has been associated with poor mental health and interpersonal relationship problems, difficulties in self-representations, and maladaptive emotion regulation [18,19].…”
Section: Introductionmentioning
confidence: 94%